2005
DOI: 10.1007/s10350-005-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

Do Geographic and Educational Factors Influence the Quality of Life in Rectal Cancer Patients With a Permanent Colostomy?

Abstract: This is the first study to show the influence of geographic origin on quality of life of patients with a permanent colostomy. Possible factors that may influence the outcome of patients after surgical treatment of rectal cancer, such as weather, religion, or culture, should be taken into account when quality of life evaluations are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 15 publications
0
32
0
4
Order By: Relevance
“…10 Although a colostomy is a well-accepted treatment for NBD, 14,15 it appears to be less well accepted in Korean culture. 11 As TAI has been suggested for disordered defecation before any irreversible surgery, 16 it could function in this way before conducting colostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Although a colostomy is a well-accepted treatment for NBD, 14,15 it appears to be less well accepted in Korean culture. 11 As TAI has been suggested for disordered defecation before any irreversible surgery, 16 it could function in this way before conducting colostomy.…”
Section: Discussionmentioning
confidence: 99%
“…10 It appears that for Korean SCIPs, bowel care habits are very individualized 10 and the choice of method is markedly influenced by the patient's sociocultural environment. 11 Moreover, as health-care systems vary widely between countries, this can be expected to influence the bowel care habits of SCIPs.…”
Section: Introductionmentioning
confidence: 99%
“…Perspectives on colostomy might be different between countries. 19 Bowel management outcomes and QoL In a previous study in Korea, gastrointestinal problems in chronic SCIPs were reported to be as high as 62.5%, which included constipation, pain during defecation, fecal incontinence and urgency. 6 These problems resulted in the deterioration of QoL in 80% and unhappiness in 62%.…”
Section: Defecation Stimulation Methodsmentioning
confidence: 99%
“…It is possible that these patients may have had problems managing their stoma due to lack of proper supportive care. In the prospective Study Group for QOL in Rectal Cancer trial, QOL for 253 APR patients from 13 institutions in 11 countries was evaluated [33]. The instrument used in this study was modified from the fecal incontinence QOL scale by Rockwood et al [34], composed of 29 items with four domains (lifestyle, coping/behavior, depression/ self-perception, and embarrassment).…”
Section: Sphincter Preservation Versus Permanent Colostomymentioning
confidence: 99%